2020
DOI: 10.3390/cells9010166
|View full text |Cite
|
Sign up to set email alerts
|

Shockwaves Suppress Adipocyte Differentiation via Decrease in PPARγ

Abstract: Adipogenesis is a crucial cellular process that contributes to the expansion of adipose tissue in obesity. Shockwaves are mechanical stimuli that transmit signals to cause biological responses. The purpose of this study is to evaluate the effects of shockwaves on adipogenesis. We treated 3T3L-1 cells and human primary preadipocytes for differentiation with or without shockwaves. Western blots and quantitative real-time reverse transcriptase PCR (qRT-PCR) for adipocyte markers including peroxisome proliferator-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…As adipocytes have vital roles in lipid metabolism to regulate energy homeostasis, lipogenesis and lipolysis are central activities often investigated to validate the intrinsic functions of these cells. ,, Such major activities of 3T3-L1 and PCS-210-010 cells after treating with noncytotoxic doses of TDB at early and late differentiation were tracked and assessed with Oil Red O staining and the contents of cellular triglyceride and glycerol released (Figure ). Cellular lipid accumulation significantly relied on differentiation inducers ( p < 0.001), supported by the absence of cellular lipid droplets stained with Oil Red O (Figure A, C, E, and G) and nearly zero percentage of Oil Red O stained (Figure B, D, F, and H) in TDB-free undifferentiated controls.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As adipocytes have vital roles in lipid metabolism to regulate energy homeostasis, lipogenesis and lipolysis are central activities often investigated to validate the intrinsic functions of these cells. ,, Such major activities of 3T3-L1 and PCS-210-010 cells after treating with noncytotoxic doses of TDB at early and late differentiation were tracked and assessed with Oil Red O staining and the contents of cellular triglyceride and glycerol released (Figure ). Cellular lipid accumulation significantly relied on differentiation inducers ( p < 0.001), supported by the absence of cellular lipid droplets stained with Oil Red O (Figure A, C, E, and G) and nearly zero percentage of Oil Red O stained (Figure B, D, F, and H) in TDB-free undifferentiated controls.…”
Section: Resultsmentioning
confidence: 99%
“…The viability of 3T3-L1 and PCS-210-010 pre-adipocytes and adipocytes was assessed using the MTT assay. , Cells were exposed for 48 h to TDB (dissolved in DMSO) on day 0 of the differentiation program (SI Figure S1) for treatment with pre-adipocytes and day 8 for treatment with adipocytes. Final concentrations at 0.5, 1, 5, 10, 25, 50, and 100 μM of TDB were tested, while the DMSO concentration per each treatment was restricted to less than 0.5%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adipogenesis is a cellular process that contributes to the expansion of adipose tissue in obesity. Obesity is a medical condition in which there is an accumulation of white adipose tissue (WAT) as a result of the hypertrophy and hyperplasia of adipocytes [ 65 ]. Mouse models show that both adipocyte size and number increase in obese adipose tissue, while human models also show that preadipocytes conserve the ability to differentiate into adipocytes and therefore continually contribute to adipose growth.…”
Section: Mechanical Response Of Adipocytesmentioning
confidence: 99%
“…A recent study evaluated the effects of shockwaves on adipogenesis. The authors demonstrated that low-energy shockwaves suppressed adipocyte differentiation by decreasing peroxisome proliferator-activated receptor γ (PPARγ) (31).…”
Section: Fig 2 Elastosonographic Scan Of the Trochanteric Region (A) ...mentioning
confidence: 99%